2014
DOI: 10.3389/fmicb.2014.00550
|View full text |Cite
|
Sign up to set email alerts
|

Activity and abundance of methane-oxidizing bacteria in secondary forest and manioc plantations of Amazonian Dark Earth and their adjacent soils

Abstract: The oxidation of atmospheric CH4 in upland soils is mostly mediated by uncultivated groups of microorganisms that have been identified solely by molecular markers, such as the sequence of the pmoA gene encoding the β-subunit of the particulate methane monooxygenase enzyme. The objective of this work was to compare the activity and diversity of methanotrophs in Amazonian Dark Earth soil (ADE, Hortic Anthrosol) and their adjacent non-anthropic soil. Secondly, the effect of land use in the form of manioc cultivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 63 publications
1
13
0
Order By: Relevance
“…The clusters are consistently found in forest soils, often as most abundant group, they are quite frequently detected in grassland soils, but rarely detected in intensively managed agricultural soils (Knief et al, 2006 ; Dunfield, 2007 ). It has been reported that populations decrease and become inactive when forest soils are converted into agricultural soils, or grasslands are subjected to grazing (Knief et al, 2005 ; Abell et al, 2009 ; Dörr et al, 2010 ; Lima et al, 2014 ). They recover in afforested or reforested sites and grassland soil in which nitrogen fertilization is reduced (Nazaries et al, 2011 ; Shrestha et al, 2012 ).…”
Section: Description Of Major Uncultivated Groups Of Methanotrophic Bmentioning
confidence: 99%
See 1 more Smart Citation
“…The clusters are consistently found in forest soils, often as most abundant group, they are quite frequently detected in grassland soils, but rarely detected in intensively managed agricultural soils (Knief et al, 2006 ; Dunfield, 2007 ). It has been reported that populations decrease and become inactive when forest soils are converted into agricultural soils, or grasslands are subjected to grazing (Knief et al, 2005 ; Abell et al, 2009 ; Dörr et al, 2010 ; Lima et al, 2014 ). They recover in afforested or reforested sites and grassland soil in which nitrogen fertilization is reduced (Nazaries et al, 2011 ; Shrestha et al, 2012 ).…”
Section: Description Of Major Uncultivated Groups Of Methanotrophic Bmentioning
confidence: 99%
“…It shows similarities in dispersal to USCγ, as it is largely absent in wetlands and acidic soils (Kolb, 2009 ; Martineau et al, 2014 ). Moreover, it shows reduced occurrence in intensively managed agricultural soils (Lima et al, 2014 ) with the exception that it has been found in some agricultural fields that are subjected to organic farming and/or that are characterized by higher carbon content (upon biochar or organic residue application; Dörr et al, 2010 ; Lima et al, 2014 ; Ho et al, 2015 ).…”
Section: Description Of Major Uncultivated Groups Of Methanotrophic Bmentioning
confidence: 99%
“…Instead, most previous work has only used high-throughput sequencing to compare soil with biochars to soil without biochars (e.g. 3 22 23 24 25 ). Consequently, much remains to be learned about the biotic communities of biochars and their metabolic potential in other soil systems.…”
mentioning
confidence: 99%
“…The primers A189f-Forest675r targeting specifically USC-α pmoA genes were used (Kolb et al 2003). We followed the protocol as described in Lima, Muniz and Dumont (2014). These assays were performed with the CFX96 qPCR cycler (Bio-Rad, München, Germany).…”
Section: Mob Abundancesmentioning
confidence: 99%